KrF laser with a power of 100 W - Panchenko Yu. N. Yury Nikolaevich; Andreev M. V. Mikhail Vladimirovich; Losev V. F. Valery Fedorovich; Puchikin A. V. Aleksey Vladimirovich (Gas and Plasma Lasers, Metal Vapor, 2015)
Title screen